Inside Cover: Creation of High‐Performance Heterogeneous Photocatalysts by Controlling Ligand Desorption and Particle Size of Gold Nanocluster (Angew. Chem. Int. Ed. 39/2021). Issue 39 (12th July 2021) - Kawawaki, Tokuhisa; Kataoka, Yuki; Hirata, Momoko; Akinaga, Yuki; Takahata, Ryo; Wakamatsu, Kosuke; Fujiki, Yu; Kataoka, Miori; Kikkawa, Soichi; Alotabi, Abdulrahman S.; Hossain, Sakiat; Osborn, D. J.; et al.
Abstract : A ligand‐desorption process during calcination was followed for metal‐oxide‐supported 2‐phenylethanethiolate‐protected gold 25‐atom metal nanoclusters (NCs) using five experimental techniques by Yuichi Negishi and co‐workers in their Research Article on page 21340 . Based on the obtained knowledge, a method to form a metal‐oxide layer on the surface of Au NCs while preventing their aggregation was established, and thereby a water‐splitting photocatalyst with high activity and stability was created.